2018
DOI: 10.1016/j.jid.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Sweat Exosome Suggests its Involvement in Skin Immunity

Abstract: Healthy human skin sustains an effective immune defense mechanism, formed by a complex physical and chemical epidermal barrier that coordinates with different cellular components of the skin immune system. However, the mechanism by which skin cells regulate local immune homeostasis in health and disease contexts is not well known. To investigate whether exosomes exist in sweat, sweat samples from healthy individuals were collected after aerobic exercise. Sweat exosome was isolated via differential ultracentrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 60 publications
5
73
0
Order By: Relevance
“…The sample was cooled down and centrifugated at 14 000 g for 15 minutes. After removing the supernatant, the filter‐aided sample preparation method was conducted . Briefly, dithiothreitol (Sigma, St. Louis, MO) was added to 30 μl of the sample at a final concentration of 100 mM.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was cooled down and centrifugated at 14 000 g for 15 minutes. After removing the supernatant, the filter‐aided sample preparation method was conducted . Briefly, dithiothreitol (Sigma, St. Louis, MO) was added to 30 μl of the sample at a final concentration of 100 mM.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs are one of them and play an important role in intercellular cellular transport and signal transduction [73][74][75]. Exosomes can transfer metabolites and promote communication between different cells through the exchange of exosomal miRNAs, and then play an immune response, tumor microenvironment remodeling and tumor metastasis during tumor progression [38,[76][77][78]. Many reports indicate that exosomes affect the biology of recipient cells by transferring miRNAs from donor cells to recipient cells, but the mechanism of how exosomes sorting miR-NAs has not been thoroughly solved.…”
Section: Mirnas Sorting To Exosomesmentioning
confidence: 99%
“…Intriguingly, EVs and their biomolecule content have been found to be released at the surface of the skin and are therefore, detectable in sweat in addition to blood and other body fluids (Wu and Liu, 2018). The study of Wu and Liu (2018) was the first and thus far only study to examine sweat EVs from healthy humans after aerobic exercise (Wu and Liu, 2018). The authors performed proteomic profiling of sweat exosomes and found sweat proteins to be enriched in EVs.…”
Section: Introductionmentioning
confidence: 99%